2008
DOI: 10.1007/s10459-008-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the academic success of first year Health Science students

Abstract: The academic success of students is a priority for all universities. This study identifies factors associated with first year academic success (performance and retention) that can be used to improve the quality of the student learning experience. A retrospective cohort study was conducted with a census of all 381 full time students enrolled in the Bachelor of Health Science at The University of Western Australia since the inception of the course in the year 2000. Factors found to be associated with successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 31 publications
8
78
0
12
Order By: Relevance
“…They found, firstly, that the higher the National Senior Certificate (NSC) 1 mark the more likely the student is to be successful and, secondly, students who did not have English as a first language are more likely to obtain a lower mark for Accounting. Mills, Heyworth and Rosenwax (2009) identified a number of factors associated with first-year students' success; the most influential being an average and above average Grade 12 mark, English as a first language and Accounting as a Grade 12 subject. Lourens and Smit (2003) confirmed that students' aggregate Grade 12 mark and main fields of learning are significant predictors of success in their first year of study at an academic institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found, firstly, that the higher the National Senior Certificate (NSC) 1 mark the more likely the student is to be successful and, secondly, students who did not have English as a first language are more likely to obtain a lower mark for Accounting. Mills, Heyworth and Rosenwax (2009) identified a number of factors associated with first-year students' success; the most influential being an average and above average Grade 12 mark, English as a first language and Accounting as a Grade 12 subject. Lourens and Smit (2003) confirmed that students' aggregate Grade 12 mark and main fields of learning are significant predictors of success in their first year of study at an academic institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[4] However, more recent studies suggest that a student's academic performance don't entirely depend on attendance but also on several other infl uencing factors. [5][6][7] While the effect of absenteeism, gender and previous academic performance on students' academic grade is well-established among students of other professional courses and foreign medical students, [6][7][8][9] the effect of the same on the grades of India medicos received little attention in the literature. Furthermore, the infl uence of place of residence on a student's academic performance was not discussed in detail in the earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the influence of the educational variables, such as the type of curriculum design, on academic failure is of key importance to actively prevent dropout. However, although there is plenty of information about the association between dropping out and student attributes [4,5], little attention has been given to examining the influence of different curriculum designs – that, by the way, have become popular in medical education across the world during the last decades (e.g., PBL, integrated-system, spiral, transdisciplinary and interdisciplinary curriculum) – on students’ withdrawal [6,7]. …”
Section: Introductionmentioning
confidence: 99%